2022
DOI: 10.3390/s23010039
|View full text |Cite
|
Sign up to set email alerts
|

Online Gamma Radiation Monitoring Using Few-Mode Polymer CYTOP Fiber Bragg Gratings

Abstract: We investigated the gamma radiation response of fiber Bragg gratings (FBGs) inscribed in a few-mode polymer optical fiber. The fiber had a graded-index CYTOP core of 20 µm and XYLEX overclad of 250 µm in diameter. Four FBGs were exposed to gamma radiation during four irradiation sessions at a 5.3 kGy/h dose rate. The FBGs showed a linear Bragg wavelength shift with the received dose with a mean sensitivity of −3.95 pm/kGy at 43 °C. The increased temperature provides a rise in the sensitivity: it reached −10.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In our previous works [7][8][9], we demonstrated that gamma radiation treatment changes the climatic properties of CYTOP FBGs: we observed a rise of the RH sensitivity with received dose and a decrease of temperature sensitivity with subsequent change of sign from positive to negative. Among irradiation doses, which we applied in the experiment, the dose of 200 kGy provided the closest to zero temperature sensitivity of the irradiated FBGs [7,8]. This case is prospective for RH sensing since temperature cross-sensitivity can be eliminated.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…In our previous works [7][8][9], we demonstrated that gamma radiation treatment changes the climatic properties of CYTOP FBGs: we observed a rise of the RH sensitivity with received dose and a decrease of temperature sensitivity with subsequent change of sign from positive to negative. Among irradiation doses, which we applied in the experiment, the dose of 200 kGy provided the closest to zero temperature sensitivity of the irradiated FBGs [7,8]. This case is prospective for RH sensing since temperature cross-sensitivity can be eliminated.…”
Section: Introductionmentioning
confidence: 59%
“…Performing the second temperature cycle at high RH (89%) straight after the cycle at 40 %RH, we faced a difficulty with temperature sensitivity precise calculation, because the BW slowly increased during the entire experiment. From our previously performed experiments with RH cycles [8], we found that the BW requires longer stabilization time in case of high RH levels and when the FBG was treated by gamma radiation. Taking this into account, we developed a program of the experiment allowing to analyze the FBG response when the RH quickly changes from high value to moderate and back, and allowing to perform the temperature cycle at stable BW (Figure 3).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, the method of gamma radiation dosimetry based on the measurement of the RIA during (or after) irradiation was investigated [19]. Finally, the response of FBGs inscribed in perfluorinated POF was examined during and after irradiation [20,21]. Recently, we tested irradiated FBGs in the environmental chamber and we found that gamma radiation increases the sensitivity of perfluorinated FBGs to relative humidity (RH) and decreases their temperature sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In the first paper, by Chapalo et al [ 1 ], the authors investigated the gamma radiation response of fiber Bragg gratings (FBGs) inscribed in a few-mode polymer optical fiber. The fiber had a graded-index CYTOP core of 20 µm and XYLEX overclad of 250 µm in diameter.…”
mentioning
confidence: 99%